Rachunek wyboru formy opodatkowania dochodów osób fizycznych prowadzących działalność gospodarczą - Poszwa, Michał (The Decisive Account of Choosing the form of Taxation on Revenue for Natural Person Running Business Activities, 2005)
In the account of tax income both revenues and costs must be taken into consideration. Proper qualification of the costs of gaining the income may cause a particular problem. It requires not only correct identification and measurement but also adequate settlements of tax costs. Those settlements concern ascribing costs to particular months and years, regarding costs of auxiliary units and right presentation of indirect costs. The way of keeping tax cost settlements influences the valuation of the correctness of tax settlements as well as the gained tax saving.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 104-116